Older Person in Society: Addressing the Social Phenomena - Balasingam, Usharani (International Journal of Engineering and Technology, 2018)
Persons over 60 years of age are categorised as older people under the United Nations (UN).Â Elder abuse has been defined as â€œa single or repeated act or lack of appropriate action, occurring within any relationship where there is an expectation of trust, which causes harm or distress to an older person, according to the World Health Organisation (WHO)â€. The form of abuse may be physical, psychological, emotional, sexual or financial abuse. It may be with or without intent. This is also seen from the perspectives of neglect, violation and deprivation. The earth has an ageing population which has brought about the need to address elder illtreatment. This universal problem faces nations across divides and boundaries and is a social issue that resonates to the core of the human heart.Â It has been reported by the WHO that is an issue with multiple facts: humanitarian, as it cause untold suffering of individuals especially if it is at the hand of loved ones, it is functional as it tear into the heart of society, it is costly as it requires societal resources and financialÂ investment, it calls for protection of the older person who is vulnerable and require safeguarding, it shapes the mores of the society and laws that should inform and guide behaviour and expectations. Furthermore it is suggested that the case of ill treatment is widespread and needs to be addressed by special services and programmes and that it is a burden as it is a cause of premature death and disability. This paper includes a review on the studies of some of the risk factors that have been conducted and some responsive protection mechanisms put in place to ensure an older person right to live a life of dignity with integrity into the older persons twilight years is protected.Â Â